Increased anti-Echinococcus granulosus antibody positivity in Fasciola hepatica infection - Muhsin KAYA; Remzi BEKTAŞ; Sadullah GİRGİN; Muttalip ÇİÇEK; Mehmet Ali KAPLAN (Turkish Journal of Gastroenterology, 2019)
-